Solvability of integral equations via the technique of measures of noncompactness - Babak Mohammadi; Mohammad Mursaleen; Vahid Parvaneh (Miskolc Mathematical Notes)
Motivated by the work of [Mohammadi et al., Mathematics, 2019, 7, 575.], we extend here Darbo’s fixed point theorem in a Banach space using the combined technique of Wardowski-Mizoguchi-Takahashi contraction. The existence of solution for a system of integral equations is provided and an example to support the effectiveness of our results is also given. Our results generalize and extend some famous comparable obtained results.